Defining and measuring long COVID fatigue: a scoping review - Deborah Edwards; Jennifer Davies; Christine Bundy; Rachael Pattinson; Bethan Thomas; Carys Dale; Benjamin Jenkins; Helena Lande (BMJ Open)
Objective Long COVID encompasses a range of symptoms in which fatigue is one of the most prevalent. It is clear from other conditions that the definition and measurement of fatigue can be complex; however, it is not clear how fatigue is defined and measured in long COVID. To advance our understanding, this review summarises the definitions and measures of long COVID fatigue being used by researchers.Design This is a scoping review that follows the JBI methodology and reports using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews.Data sources Medline, Scopus, CINAHL, PsycINFO, EMCARE, Web of Science, Epistemonikos, Cochrane Central Register of Controlled Trials, Dimensions, Overton and ProQuest Dissertations & Theses databases were searched from January 2020 to May 2023.Eligibility criteria This review included quantitative and qualitative studies that included any definition of long COVID and/or measurement tool that purported to quantify either the impact, severity or symptoms of long COVID fatigue.Data extraction and synthesis Two independent reviewers screened the title, abstract and full text of the selected studies based on the inclusion criteria. Data extraction was performed by two independent reviewers. The data were summarised in tabular format and a narrative summary.Results The search retrieved 9839 studies, of which 57 met the inclusion criteria. Only 21 (37%) provided a definition of fatigue. Definitions ranged across physical, mental, cognitive, emotional, psychosocial, central, peripheral, postexertional symptom exacerbation and general dimensions of fatigue. Fifty-five (96%) used a measurement or assessment of fatigue. Twenty-six measures of fatigue were identified: 21 self-report measures (eg, Fatigue Assessment Scale) and 5 fatigability measures that purport to reflect changes in physiological processes that contribute to or reflect fatigue (eg, change in the force generating capacity of a muscle).Conclusions The definitions identified demonstrate considerable diversity, each highlighting different dimensions of long COVID fatigue. Long COVID fatigue was predominantly measured through self-report methods, which is problematic. There is an urgent need to better understand long COVID fatigue and to identify the different mechanisms involved. In order to do this, we need consistency with the language around fatigue and its measurement within research and across disciplines.Review registration The protocol has been registered on Open Science Framework (https://doi.org/10.17605/OSF.IO/HNF8Z).